2022
DOI: 10.1063/5.0131123
|View full text |Cite
|
Sign up to set email alerts
|

The effect of defect and substitution on barocaloric performance of neopentylglycol plastic crystals

Abstract: Plastic crystal neopentylglycol (NPG, C5H12O2) has become an important candidate material in the future solid-state refrigeration field due to its huge colossal barocaloric effects near room temperature. However, NPG encounters significant shortcomings in practical cooling process that hinders its further application. Here, we systematically investigate the effect of defects and substituting a small amount of additional alien molecules on the barocaloric performance of NPG plastic crystals. It is found that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This further suggests that methods of influencing S-S recrystallisation processes may result in different FOPT behaviour on cooling. It is important to note that we have presented an example of thermal hysteresis variation that is independent of sample geometry or the presence of additional inclusions, which have been discussed in the recent NPG literature [14,[30][31][32]. We have additionally demonstrated the strength of combining multiple imaging techniques in the study of BC materials, specifically in the ability to link microstructure with spatio-temporal thermal processes during their FOPTs.…”
Section: Discussionmentioning
confidence: 72%
“…This further suggests that methods of influencing S-S recrystallisation processes may result in different FOPT behaviour on cooling. It is important to note that we have presented an example of thermal hysteresis variation that is independent of sample geometry or the presence of additional inclusions, which have been discussed in the recent NPG literature [14,[30][31][32]. We have additionally demonstrated the strength of combining multiple imaging techniques in the study of BC materials, specifically in the ability to link microstructure with spatio-temporal thermal processes during their FOPTs.…”
Section: Discussionmentioning
confidence: 72%
“…Another way is connected not only with the search for 'champions' in the field of extensive BCE, but also with attempts to find methods for purposeful control and tuning of physical/barocaloric properties [14,20,21]. The study of several families of crystals with cubic and orthorhombic structures created by cation/anion substitutions has shown that chemical pressure is one of the most effective tools for achieving this goal [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has recently been shown that the area of applicability of such materials can be extended. Comparative analysis of the barocaloric efficiency of materials of different physical origin [7,14,24,25] showed that some fluorides and oxyfluorides with octahedral and/or quasi-octahedral anionic polyhedra, [MF 6 ]/[MF 6−x O x ], in the structure, demonstrating outstanding barocaloric parameters [20,21] are competitive candidates for use as effective refrigerants in alternative cooling technologies based on BCE in solids.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, barocaloric materials have been demonstrated to exhibit very large thermal changes, some of them as large as Δ S ≥ 100 J K −1 kg −1 (the same order of magnitude as refrigerant gases) under the application of low/moderate pressures of p = 70–1000 bar (while refrigerant gases normally operate at p ≤ 150 bar). 17–34 These barocaloric materials belong to many different families of compounds, such as ammonium or phosphate salts, 35–43 superionic conductors, 44,45 spin crossover materials, 46–52 n -alkanes, 53 hybrid organic–inorganic materials, 54–61 organic plastic crystals 62–69 and polymers. 70–72 Even more recently, barocaloric effects have been combined with gas adsorption/desorption processes in solid-to-solid breathing-transitions in MOFs, giving rise to larger thermal changes of Δ S ∼ 300 J K −1 kg −1 under pressures as small as p ≤ 16 bar.…”
Section: Introductionmentioning
confidence: 99%